A Cost-Effective QR Code-Based Equipment Management System for Small-Scale Clinical Facilities - Phong-Luu Nguyen; Dinh-Hai Vu; Trong-Bang Tran (PT. Teknologi Futuristik Indonesia, 2026)
The rapid proliferation of medical devices in clinical settings necessitates efficient tracking and maintenance to ensure healthcare quality and cost optimization. (Gap) Despite technological advancements, many small to medium-sized clinics continue to rely on manual, paper-based equipment management systems. These traditional methods are prone to human error, lack real-time monitoring, and suffer from inefficient audit trails. (Objective) This study aims to develop a cost-effective, QR code-based equipment management system tailored specifically for small-scale clinical facilities. The proposed system integrates a Flutter-based cross-platform application with a centralized PostgreSQL database, utilizing standard webcams for QR code scanning to eliminate the need for expensive, dedicated scanning hard-ware. (Findings) Experimental implementations demonstrate that the system achieves a >95% QR code identification success rate at optimal scanning distances (0.3–1.0m) under standard lighting. Further-more, the architecture guarantees 99.2% network uptime, seamless real-time data synchronization, and supports up to 20 concurrent users with low database query latency (15–30 ms). Cost analysis indicates significant economic advantages, with first-year operational costs ranging from 300 to 600, markedly lower than commercial alternatives. (Implications) By replacing outdated manual methods with an auto-mated, role-based tracking system, this solution provides clinics with a robust, accessible, and scalable tool to enhance operational efficiency and streamline equipment lifecycle management.